Culture 2025 A National Cultural Policy Framework for Ireland. Issue 2 (14th March 2020) - Hadley, Steven; Collins, Patrick; O'Brien, Maria
ABSTRACT: Published in January 2020, Culture 2025 A National Cultural Policy Framework for Ireland is the first single national cultural policy in Ireland since the formation of the Irish State in 1922. We outline the development and content of the framework – including its principles, aims and values – in the context of both Irish cultural policy history and the "whole-of-government" policy approach. To interrogate the coherence of the policy framework, we focus on the creative industries in general, and the audiovisual sector, in particular. We question whether Culture 2025's, broad incorporation of various sectors (language, arts, heritage, and creative industries), can say anything of significance about the promotion of culture in Ireland. Through the integration of pre-existing strategies into the Irish economic system, we argue that Culture 2025 presents itself as the only realistic approach to culture and the arts in the form of a "cultural policy realism".